A primary tumour of the oesophagus with both melanocytic and schwannian differentiation. Melanocytic schwannoma or malignant melanoma?. Issue 4 (1st April 2002) - Brown, R M; Darnton, S J; Papadaki, L; Antonakopoulos, G N; Newman, J
Abstract : A 76 year old white woman presented with a four month history of dysphagia and weight loss. Clinical, radiological, and endoscopic examination revealed a pigmented mass in the lower third of the oesophagus. The preoperative diagnosis, including biopsy examination, was that of malignant melanoma. Following oesophageal resection, the mass was found to be a localised, relatively superficial tumour with light, electron microscopic, and immunohistochemical features common to both Schwann cells and melanocytes. The patient survived 46 months after surgery and died of a stroke, with no evidence of tumour recurrence. The tumour is presented as a case of melanocytic schwannoma, with unique features when compared with oesophageal melanotic schwannomas and malignant melanomas described in the literature. The differential diagnosis is discussed and an origin from a common precursor cell of neural crest origin is postulated.